Nasal Transmissible Venereal Tumor (TVT) with Bone Metastasis in a Dog - Silva, Iury de Azevedo Rodrigues; Marinho, Amanda Freitas Santiago; da Fonseca, Thaisa de Oliveira Paes; Tôrres, Lolaide Alves Garcia; de Carvalho, Eliane do Socorro Pompeu; Marques, Larissa Coelho; Paredes, Laura Jamille Argolo (Acta Scientiae Veterinariae, 2022)
Background: Transmissible venereal tumor (TVT) is a highly contagious round cell neoplasm that affects dogs, and it is usually transmitted through coitus. The tumor is mainly located in the genital area; however, the neoplasm can also be extragenital, affecting the nose, mouth, and eyes, as well as the skin and superficial lymph nodes. Cytological examination is the most commonly used method for definitive diagnosis due to its low cost and fast execution. Chemotherapy, radiotherapy, surgical resection, and other procedures such as cryosurgery are the possible treatment options. The objective of this report was to describe a case of extragenital TVT with nasal primary site and metastasis in the bone tissue in a dog treated at a private veterinary hospital in the city of Belém, Pará, Brazil. Case: A 6-year-old male domiciliary Labrador Retriever dog, weighing 24.2 kg, received oncologic treatment in a private veterinary hospital in the city of Belém, Pará, Brazil. The animal had a history of neoplastic disease, and he had undergone TVT resection associated with chemotherapy treatment more than 3 years ago. The clinical examination revealed a volume increase in the periorbital region, left lateral ocular displacement, left nostril excessive epistaxis, recurrent sneezing, cough, and pain signs, and tumor metastasis was suspected. Complementary exams of oncological cytology, computed tomography (CT), hemogram, and serum biochemistry were requested for diagnosis and staging of the condition, and supportive therapy was prescribed. The cytological report showed a dense population of neoplastic round cells with characteristics of TVT. CT indicated the presence of a heterogeneous hypodense mass with irregular contours and partially defined limits, with slight uptake of the intravenously injected contrast medium that obliterated the nasal cavity, maxillary recess, nasopharyngeal meatus, frontal sinus, and sphenoid sinus on the left side. The hematological analysis revealed mild anemia, neutrophilia, and lymphopenia, while the biochemical analysis only showed hypocalcemia. The prescribed therapy was amoxicillin + potassium clavulanate, omega-3, firocoxib, tranexamic acid, and finally chemotherapy with lomustine. Since the patient did not return for follow-up, the outcome could not be determined. Discussion: The patient described in this report was a domiciliary dog who did not live with other pets, but had access to the community environment and contact with other animals. The animal’s history, clinical signs, and cytological and imaging findings were consistent with those of TVT. In extragenital presentations of TVT, the inguinal and sublumbar lymph nodes, lungs, and abdominal organs are most commonly affected. Furthermore, bone involvement is rare, as this has not been commonly described in the literature as compared to the other sites of metastases. An abrasive brush was used for the cytological sample collection, because it provides slides with richer cells as compared to the imprint samples. CT is an important tool for the diagnosis of neoformations in the skeleton, and this method demonstrated high efficiency in identifying the bone involvement and the degree of the invasion and lesion in this case. The therapeutic agents used in this case were different from the usual, since the patient was given lomustine (40 mg/capsule, orally) in the metronomic chemotherapy. This drug has been previously used as an alternative in a canine TVT case resistant to vincristine. Keywords: neoplasm, extragenital, computed tomography, TVT. Título: Tumor Venéreo Transmissível (TVT) nasal com metástase óssea em um cão Descritores: neoplasia, extragenital, tomografia computadorizada, TVT.